The Application of Mind Mapping Method to Improve Subject Writing English Main Topics Analytical Exposition Text for class 11 students North Sumatra Hajj Health Vocational School - Chairunnissa Chairunnissa (Education Achievement: Journal of Science and Research, 2024)
This research aims to determine the skills of class This research is classroom action research using two cycles. The research instruments used were observation sheets and written tests. Based on the results obtained, observations showed that the average for the first cycle was 53%, while for the second cycle, it was 83%. This shows increased cooperation, activeness, and changes in student learning outcomes. From the results of the written test on mastery of analytical exposition text writing material, the average score for the first cycle was only 68.39 with students not yet reaching the KKM of 80. Meanwhile, in the second cycle, the average score for the written test reached 82.50, with students achieving the expected KKM. the. It proves that the action hypothesis can be achieved, so applying the Mind Mapping technique can improve the ability to write analytical exposition text of Class XI students at the Hajj Health Vocational School, North Sumatra.